Faktor Yang Memengaruhi Kinerja Karyawan: Kajian Studi Literatur Manajemen Sumber Daya Manusia - Anita Sukmawati; Sri Sundari; Marisi Pakpahan (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Previous research or relevant research has a very important role in a scientific work. Through previous or related research, theories and relationships or influences between variables can be strengthened. This article reviews the factors that influence how employee performance is influenced by the work environment, job satisfaction, and commitment to the organization in a literature review in the field of Human Resource Management. The findings from this research literature are that: 1) the work environment influences employee performance; 2) job satisfaction influences employee performance; 3) and commitment to the organization influences employee performance.